qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 6 \left ( x + 1 \right )$
$y = 2 x + 10$
$x$Intercept
$\left ( - 1 , 0 \right )$
$y$Intercept
$\left ( 0 , 6 \right )$
$x$Intercept
$\left ( - 5 , 0 \right )$
$y$Intercept
$\left ( 0 , 10 \right )$
$6 \left( x+1 \right) = 2x+10$
$x = 1$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ 6 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 2 x + 10$
$ $ Multiply each term in parentheses by $ 6$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } = 2 x + 10$
$6 x + 6 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 10$
$ $ Move the variable to the left-hand side and change the symbol $ $
$6 x + 6 \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = 10$
$\color{#FF6800}{ 6 } x \color{#FF6800}{ + } \color{#FF6800}{ 6 } - 2 x = 10$
$ $ Move the constant to the right side and change the sign $ $
$6 x - 2 x = 10 \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = 10 - 6$
$ $ Organize the expression $ $
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = 10 - 6$
$4 x = \color{#FF6800}{ 10 } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$ $ Subtract $ 6 $ from $ 10$
$4 x = \color{#FF6800}{ 4 }$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ 4 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ 1 }$
Solution search results
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo